Profil Kinerja Finansial Perusahaan-Perusahaan Yang Go-Public Di Pasar Modal Asean - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Almost all companies listed in ASEAN country capital markets have dropped their financial performance since the accounting year of 1997. In Indonesia, more than sixty per cent of companies listed in Jakarta Stock Exchange did not or did not dare to publish their mandatory annual financial statements to avoid publishing their poor performance. The similar situation has also been felt by other ASEAN country capital markets. The question that was relevant to be raised: are the poor financial performance of companies listed in the ASEAN country capital markets caused by the sudden crisis or by long experience ofpoor financial performance? This study intents to answer the above question, whether the crisis or longtime of poor financial performance caused the company financial problems. Samples were taken from companies listed in four major capital market of ASEAN, namely: Thailand, Singapore, Malaysia, and Indonesia. Pooled time series data consist of 132 data included in the sample for three year periods of 1993, 1994, and 1995 for 44 companies. The parametric and non parametric statistic methods of t-tests, Wilcoxon Ranks Sign Test, MANOVA, and Friedman K-Samples were used to test the hypothesis. The results indicate that Thailand has the weakest financial performance, followed by Indonesia, Singapore, and then Malaysia, when they are compared to the empirical standards of financial performance. This study used The standards of financial performance that were introduced by Beaver (1966 and 1968), Altman (1968), and Zmejewski (1984). Intuitively, this study concluded that the poor financial performances have already long been suffered by companies listed in ASEAN country capital markets before the monetary crisis. The crisis has just opened the hidden problems.